Clinical pharmacological innovation in the treatment of depression. Issue 4 (3rd April 2023) - Witkin, Jeffrey M; Golani, Lalit K; Smith, Jodi L
ABSTRACT: Introduction: Deficiencies in standard of care antidepressants are driving novel drug discovery. A new age of antidepressant medications has emerged with the introduction of rapid-acting antidepressants with efficacy in treatment-resistant patients. Areas covered: The newly approved medicines and those in clinical development for major depressive disorder (MDD) are documented in this scoping review of newly approved and emerging antidepressants. Compounds are evaluated for clinical efficacy, tolerability, and safety and compared to those of standard of care medicines. Expert opinion: A new age of antidepressant discovery relies heavily on glutamatergic mechanisms. New medicines based upon the model of ketamine have been delivered and are in clinical development. Rapid onset and the ability to impact treatment-resistant depression, raises the question of the best first-line medicines for patients. Drugs with improvements in tolerability are being investigated (e.g. mGlu2/3 receptor antagonists, AMPA receptor potentiators, and novel NMDA receptor modulators). Multiple companies are working toward the identification of novel psychedelic drugs where the requirement for psychedelic activity is not fully known. Gaps still exist – methods for matching patients with specific medicines are needed, and medicines for the prevention of MDD and its disease progression need research attention.